2020
DOI: 10.1097/mnm.0000000000001317
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body 18-F-FDG-PET in patients with leptomeningeal disease and correlation with MRI

Abstract: Objective Studies evaluating leptomeningeal disease on whole-body 18F-FDG PET are lacking. The purpose was to evaluate PET imaging of leptomeningeal disease and investigate the incremental utility of newer PET reconstructions in leptomeningeal disease. Methods PET imaging of 56 patients with leptomeningeal disease detected initially on MRI (n = 53) or cytopathology (n = 35) were retrospectively reviewed. Regular 3-dimensional iterative reconstruction (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, there is no consensus on the optimal choice of background reference regions for spinal PET analysis. Previous studies have suggested various anatomical structures, including supratentorial brain tissue [2], the aortic blood pool [21], the liver blood pool [22][23], the spinal cord at C7/T1 [4], the distal spinal cord [24][25], and different segments of the spinal cord [26], as potential background regions. However, the proposed regions vary signi cantly in their anatomical extent, spanning across several body parts.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no consensus on the optimal choice of background reference regions for spinal PET analysis. Previous studies have suggested various anatomical structures, including supratentorial brain tissue [2], the aortic blood pool [21], the liver blood pool [22][23], the spinal cord at C7/T1 [4], the distal spinal cord [24][25], and different segments of the spinal cord [26], as potential background regions. However, the proposed regions vary signi cantly in their anatomical extent, spanning across several body parts.…”
Section: Introductionmentioning
confidence: 99%